THE INNOVATIVE TERRITORIAL CLUSTER LIFE CYCLE IN THE OIL AND GAS INDUSTRY - E. Karkhanova (Вестник университета)
The life cycle of the innovative territorial cluster in the oil and gas industry were investigated. The approaches of such scientists, as G.B. Kleiner, R.M. Kachalov, N.B Nagrudnaya, R. Martin, P. Sanley and others were studied. Such phases of the cluster life cycle as creation, development and growth, stabilization, decline and release, reorganization and restructuring has been identified. The relationship between the drivers and barriers of the cluster life cycle development has been proved. Digital transformation is presented as a factor that can extend the stage of development and growth of the cluster